Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd006146
|View full text |Cite
|
Sign up to set email alerts
|

Opioids for neuropathic pain

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 67 publications
2
85
0
6
Order By: Relevance
“…While reporting contradictory results, Eisenberg et al 's study of 23 trials showed overall relief ranging from 8 to 70 days, with all trials demonstrating opioid efficacy [33]. Deshpande et al, in a Cochrane Collaboration review of opioids for chronic low back pain, found only one trial comparing morphine or oxycodone to naprosyn, and three trials meeting inclusion criteria compared tramadol to placebo and concluded that there was no significant benefit with morphine or oxycodone, whereas tramadol was more effective than placebo for pain relief and improvement of function [34].…”
Section: Short-term Effectivenessmentioning
confidence: 97%
See 1 more Smart Citation
“…While reporting contradictory results, Eisenberg et al 's study of 23 trials showed overall relief ranging from 8 to 70 days, with all trials demonstrating opioid efficacy [33]. Deshpande et al, in a Cochrane Collaboration review of opioids for chronic low back pain, found only one trial comparing morphine or oxycodone to naprosyn, and three trials meeting inclusion criteria compared tramadol to placebo and concluded that there was no significant benefit with morphine or oxycodone, whereas tramadol was more effective than placebo for pain relief and improvement of function [34].…”
Section: Short-term Effectivenessmentioning
confidence: 97%
“…Consequently, numerous reviews have been published evaluating opioid therapy in chronic noncancer pain, with variable opinions [21,22,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Opioids In Chronic Noncancer Painmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40] The validity, clinical relevance, and applicability of the evidence for peripheral and central NeuP in South Africa were discussed.…”
Section: Evidence Evaluationmentioning
confidence: 99%
“…38,80 In head-tohead comparisons, opioids provided at least as much analgesia as TCAs and gabapentin. 81,82 Despite strong evidence of efficacy, most of the international guidelines reserve opioid analgesics as second-or third-line agents mainly because of risk of long-term side-effects and possible opioid misuse and addiction.…”
Section: Opioids (Tramadol Morphine and Methadone)mentioning
confidence: 99%
“…Opioids and other traditional analgesics, such as non-steroidal anti-inflammatory drugs (NSAIDs), are the cornerstone of nociceptive pain management. Although evidence is emerging of the efficacy of opioids in controlling neuropathic pain, 1 antidepressants and anticonvulsants are considered first-line in the treatment of neuropathic pain.…”
mentioning
confidence: 99%